Refleksija društvenog i kulturnog okruženja u muzici za predstave pozorišta u Šapcu i Bitolju u periodu 1950.–1990. godine - Bužarovski, Dimitrije; Đurković-Pantelić, Milena; Jordanoska, Trena (University of Silesia Press, 2020)
Istraživanje o refleksiji društvenog i kulturnog okruženja u muzici za predstave koje su postavila pozorišta u Šapcu i Bitolju, dva grada u različitim republikama bivše SFRJ, polazi od pretpostavke da oba pozorišta povezuje više zajedničkih crta. Najpre ih ujedinjuje njihova geopolitička pozicija, jer oba grada predstavljaju tromeđu: Šabac je između Srbije, Bosne i Hrvatske, a Bitolj između Makedonije, Grčke i Albanije. Osim toga, Bitolj i Šabac su bili veoma važni kulturni i administrativni centri još u XIX veku. To su područja na kojima se ukrštaju orijentalni i okcidentalni kulturni idiomi, poznati su kao gradovi prvih klavira u Srbiji i Makedoniji, i u vreme SFRJ već imaju višedecenijsku pozorišnu tradiciju. Istraživanje se bazira i na pretpostavci da su na teritoriji bivše SFRJ postojali slični kulturni modeli kao rezultat društveno-političkog, ekonomskog, kulturnog i obrazovnog okruženja. Istraživanje je ograničeno na period 1950–1990. godine, da bi se ublažile direktne posledice Drugog svetskog rata kao i IB-a 1948, odnosno, kada se uspostavio jedan stabilniji period koji se zaokružuje sa početkom raspada SFRJ, 1990. godine. U ovom periodu, u Šapcu su premijerno izvedene 284 pozorišne predstave, a u 103 je korišćena muzika (prema dostupnim informacijama za 59 predstava autorska, a za 44 predstave ilustracije), dok je u Bitolju premijerno odigrano 278 predstava i u 113 je korišćena muzika (21 put autorska, 92 puta ilustracije). Istraživanje polazi od repertoara (dramski pisci, predstave i režiseri), da bi se suzilo i baziralo na upotrebu muzike u njemu. Pri tome, pretpostavka je da karakteristike upotrebljene muzike i posebno žanrovske i stilske preferencije režisera, reflektuju društveno i kulturno okruženje SFRJ. Isto tako, u dizajniranju istraživanja pošli smo i od pretpostavke da su tehničko okruženje (koje je stajalo na raspolaganju režiseru i koje se značajno menjalo u toku četiri decenije), kao i ekonomsko okruženje (mogućnost da se angažuju kompozitori i ansambli za izvođenje i snimanje muzike, ili se koriste muzički ilustratori), bitno uticali na nivo i dinamiku zastupljenosti muzike u analiziranom repertoaru. / The research on the reflection of the social and cultural environment in the music for plays set by the theaters in Šabac and Bitola, two cities in different republics of the former SFR Yugoslavia, is based on the assumption that both theaters have much in common: the geopolitical tripoint position of the cities (Šabac – Serbia, Bosnia, Croatia; Bitola – Macedonia, Greece, Albania), both cities were important cultural and administrative centers in the Balkans in the XIX century, those were the regions where Oriental and Occidental cultural idioms were crossed, apparently those were the cities with the first pianos in Serbia and Macedonia, and at the time of SFRY they already had almost century-old theater tradition. The research is based on the assumption that similar cultural models existed in the regions of the former SFRY as a result of the socio-political, economic, cultural and educational environment. The research is limited to the period 1950–1990 in order to mitigate the direct consequences of the World War Two, as well as IB 1948, i.e., to be established a more stable period, which is rounded off with the onset of the SFRY break-up in 1990. In this period, 284 theater performances were premiered in Šabac, 103 of which were plays with a use of music (59 with original music, 44 with adaptation of music), while 278 plays were premiered in Bitola, 113 of which music was used (21 with original music, 92 with adaptation of music). The research begins with the repertoire (playwrights, plays and directors) in order to focus on the use of music in the plays. In addition, the assumption is that the characteristics of the music used, and especially the genre and stylistic preferences of the director, reflect the social and cultural environment of the SFRY. Likewise, in the research design we also assumed that the technical environment (which was available to the director and which changed significantly over the course of four decades), as well as the economic environment (the ability to engage composers and ensembles for performing and recording music, vs someone who will only make adaptation of music to the play), significantly influenced the level and dynamics of the representation of music in the analyzed repertoire. Based on the collected empirical data, analysis and comments, we could conclude that music for plays is a very important indicator regarding the social and cultural changes in SFRY. There is an evident parallelism between the activities of the theatres in Šabac and Bitola. This is confirmed by: the average number of plays, repertoire policy, and the number of plays with composed or adapted music. The data confirmed that there was a significant level of the cultural integration on SFRY territory and that the changes in the repertoire and the usage of music reflected the social, political and cultural changes both in and out of SFRY. This was particularly evident in the democratization processes after the 1970s which led to the opening towards the western cultural trends.
Reflection of the social and cultural environment in the incidental music in Šabac and Bitola theaters from 1950 to 1990
Keywords: music for plays, SFRY, cultural environment, genre, style